2003
DOI: 10.1080/08035320310001491
|View full text |Cite
|
Sign up to set email alerts
|

Short-term ceftriaxone therapy for treatment of severe non-typhoidal Salmonella enterocolitis

Abstract: High CRP, prolonged high fever and signs of moderate or severe dehydration appear appropriate to define severe cases of Salmonella enterocolitis. Short-course ceftriaxone therapy is clinically beneficial to these patients. Neither clinical nor microbiological relapse was seen after therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several studies have revealed that the short-term use of ceftriaxone in pediatric patients with severe nontyphoid salmonellosis may improve the clinical course. 19,24,25 However, to the best of our knowledge, no previous study has determined whether ceftriaxone use prolongs or shortens the fecal excretion time of NTS. In the present study, although the rate of ceftriaxone use was higher in group A than group I, ceftriaxone did not shorten the fecal excretion time of NTS in the analysis.…”
Section: + Modelmentioning
confidence: 99%
“…Several studies have revealed that the short-term use of ceftriaxone in pediatric patients with severe nontyphoid salmonellosis may improve the clinical course. 19,24,25 However, to the best of our knowledge, no previous study has determined whether ceftriaxone use prolongs or shortens the fecal excretion time of NTS. In the present study, although the rate of ceftriaxone use was higher in group A than group I, ceftriaxone did not shorten the fecal excretion time of NTS in the analysis.…”
Section: + Modelmentioning
confidence: 99%
“…Antimicrobial treatment options for adults include ceftriaxone, a medically important third-generation cephalosporin, and fluoroquinolones. There are potential side effects of fluoroquinolones for paediatric patients, and hence the first choice of treatment is ceftriaxone 2 4 . Because fewer treatment options are available for antimicrobial-resistant Salmonella , infections with these strains are potentially more life threatening 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the clinical resolution of symptoms is typically slower with ceftriaxone than with ciprofloxacin, and more severe cases may require courses longer than five days. The effectiveness of ceftriaxone has been demonstrated in the treatment of both typhoid [95] and non-typhoid salmonellosis [96] and shigellosis [83,97], even with strains resistant to fluoroquinolones [98,99]. Besides the need for parenteral administration and the high cost, the major drawback of the widespread empirical use of ceftriaxone for the treatment of acute infectious diarrhea is the immediate danger of increasing microbial resistance to this useful drug.…”
Section: Third Generation Cephalosporinsmentioning
confidence: 99%